(untitled) (Journal of University of Babylon for Engineering Sciences, 2018)
There are different pollution sources, which affect soil including transportation, especially in highways. These effects can be assessed by Environmental Impact Assessment. In this study, seven sampling stations were selected in different distances (0, 10, 20, 50, 100 meter) along Tehran- Karaj highway. Samples were collected and their concentrations of Pb were measured using a FAAS after dry acid digestion. It was observed that the highway had a negative impact on the peripheral soil. These impacts were higher in Tehran with average lead concentrations, and declined by moving toward Karaj. Moreover, the average concentration of lead in soil significantly decreased by increasing distance from the roadside. Highest lead concentration was in station (E) in the middle of the road with an average of 160.50 mg/kg. The highest average concentrations were observed in soils of the roadside with an average of 115.25 mg/kg. The highest concentration was also observed in station (B) and in the roadside, with a concentration of 302 mg/kg, which was above the international allowable limits. Tehran- Karaj highway is in the list of the most polluted roads in the world and it must be concerned for its lead pollution, especially in the roadside. Essential steps for controlling the negative impacts must be taken including the expansion of green-space along the highway.